IOL power calculations after LASIK or PRK: Barrett True-K biometer-only calculation strategy yields equivalent outcomes as a multiple formula approach. Issue 7 (July 2022) - Ferguson, Tanner J.; Downes, Rachel A.; Randleman, J. Bradley
Abstract : Using the Barrett True-K integrated into the biometer provided equivalent outcomes vs a multiple formula approach for IOL power calculations in both postmyopic and posthyperopic refractive surgery eyes. Abstract : Purpose: To compare the accuracy of intraocular lens (IOL) power calculations performed using the biometer-embedded Barrett True-K formula vs a multiple formula approach using the ASCRS postrefractive calculator in eyes with previous myopic or hyperopic refractive surgery. Setting: Cole Eye Institute, Cleveland Clinic, Cleveland, Ohio. Design: Retrospective, consecutive case series. Methods: Patients who underwent cataract surgery with a history of corneal refractive surgery were included. For each formula, the IOL prediction error and refractive prediction error was calculated. Main outcome measures included mean absolute error (MAE) and the percentage of eyes within ±0.25 diopters (D), ±0.50 D, and ±1.00 D. Results: 96 postmyopic eyes and 47 posthyperopic eyes were analyzed. In the postmyopic cohort, the Barrett True-K formula had the lowest MAE (0.36 D), followed by the Haigis-L formula (0.41 D). The Barrett True-K formula had a significantly higher percentage (44.8%) of eyes within ±0.25 D in comparison with the Haigis-L formula (34.4%), which had the second highest percentage ( P < .01). In the posthyperopic cohort, the Barrett True-K formula had the lowest MAE (0.41 D), followed by the ASCRS–mean (0.46). The Barrett True-K and ASCRS–mean formulas had the highest percentage of eyes within ±0.25 D (42.6% vs 38.3%, P = .16). Conclusions: The Barrett True-K formula built into the biometer performed equivalently to a multiple formula approach on the ASCRS online calculator in both postmyopic and posthyperopic eyes. This approach reduces the potential for transcription error from data entry for lens power calculation approaches that require manual data entry.